Methods of Market Approach in business valuation in the Czech conditions - Krch, Přemysl (2010)
The purpose of the diploma thesis was to assess the applicability of Market Approach in business valuation of the Czech entities. The first part comprises basic description of Valuation methods, the core of the thesis describes the guideline publicly traded companies method - multiples, comparable companies etc. -, guideline transaction method and industry multiples method. The application part consists of two valuations using guideline publicly traded companies method - the valuation of Komercni banka and of Trinecke zelezarny.